Cytomegalovirus and Langerhans Cell Histiocytosis: Is There a Link? - Khoddami, Maliheh (Iran J Pediatr, 2016)
BACKGROUND: Langerhans cell histiocytosis is a rare proliferative histiocytic disease of unknown etiology. Histologically, it is characterized by granuloma-like proliferation of Langerhans-type dendritic cells derived from bone marrow. Many investigators have suggested the possible role of viruses such as Epstein-Barr virus, human herpesvirus-6 (HHV-6), herpes simplex virus (HSV) types 1 and 2, and Cytomegalovirus in the pathogenesis of Langerhans cell histiocytosis. OBJECTIVES: In this study, we have investigated the presence of Cytomegalovirus in Langerhans cell histiocytosis in Iranian children. PATIENTS AND METHODS: In this retrospective study, we have investigated the presence of Cytomegalovirus DNA expression, using paraffin-embedded tissue samples of 30 patients with Langerhans cell histiocytosis and 30 age and site-matched controls by qualitative Polymerase Chain Reaction (PCR) method. RESULTS: No significant difference in prevalence of Cytomegalovirus presence between patients and controls was found. Cytomegalovirus was found by qualitative PCR in only 2 (6.66%) out of 30 patients and in 1 (3.3%) of 30 control samples with a P value of 1 (1.00 > 0.05) using chi-square test with OR: 2.07; 95% CI of OR: 0.18 - 24.15. CONCLUSIONS: Our findings do not support the hypothesis of a possible role for Cytomegalovirus in the pathogenesis of Langerhans cell histiocytosis.